Warehouse storage assignment: The case study of a plastic bag manufacturer - C. Kasemset (2018)
© 2014 IEEE. This study presents the application of storage assignment in warehouse management to the case study of a plastic bag manufacturer located in Thailand. The objective is to evaluate the performance of the two methods: (1) using mathematical model and (2) class-based policy. The studied warehouse had one I/O point with 287 storage units dedicated for 62 products. The results of the mathematical model gave 51,317.45 meters per month as a minimum total traveling distance. The class-based policy gave 55,394.46 meters per month. Currently, non-systematic approach gave 71,921.38 meters per month (reduction from mathematical model and class-based methods were 28.65% and 22.98% respectively). The results from mathematical model is the optimal solution but to implement this policy, information technology such as warehouse system management was recommended to support workers during picking and receiving products.